Performance of New Muchamiel Tomato Lines with Virus Resistance Genes Grafted onto Two Commercial Rootstocks - Pedro Carbonell; José Ángel Cabrera; Juan Francisco Salinas; Aránzazu Alonso; Adrián Grau; Lucía Sánchez-Rodríguez; Joaquín Parra; Julián Bartual; Raul Martí; Jaime Cebolla-Cornejo; Juan J. Ruiz; Santiago García Martínez (Agronomy, 2022)
Tomato landraces are regaining interest in Spain because their great fruit quality and value in popular gastronomy. Muchamiel is a traditional tomato variety grown in SE Spain that has been recently improved by the CIAGRO-UMH Tomato Breeding Group, resulting in several lines and hybrids with genetic resistances to virus and most of the original Muchamiel genome. In the current study, two hybrids and one pure line from CIAGRO-UMH and a commercial Muchamiel were grown under conventional conditions to evaluate three different grafting treatments: non-grafting and grafting onto the commercial Beaufort and Maxifort rootstocks. The yield parameters and fruit quality were assessed, and a sensory analysis was performed to evaluate the behavior of every scion/rootstock combination. Overall, significantly worse yield and fruit number in Maxifort-grafted plants were reported; as well as a slight reductions in SSC, fructose, and sucrose; and significant effects on few sensory traits. Instead, Beaufort-grafted plants showed no reduced yield, whereas no differences were reported between grafting treatments in fruit weight, TA, and acid profile, as well as in most of flavor and texture sensory parameters. These results suggest that Muchamiel/Beaufort combination could be suitable under unfavorable conditions, while Maxifort do not seem to provide agronomic nor quality benefits.